Choroid plexus-mediated CSF secretion remains stable in aging rats via high and age-resistant metabolic activity - Sara D. Lolansen; Eszter O. Révész; Søren N. Andreassen; Marleen Trapp; Chiara Salio; Marco Sassoé-Pognetto; Jens Velde Andersen; Emil W. Westi; Trine L. Toft-Bertelsen; Jonathan H. Wardman; Anne-Kristine Meinild Lundby; Flemming Dela; et al. (Nature Communications)
Abstract Our brain is bathed in cerebrospinal fluid (CSF) that is produced by the choroid plexus. CSF serves as a dispersion route for hormones and nutrients, and a conduit for waste clearance. Age-dependent reduction in the CSF secretion rate could influence cerebral waste clearance and thereby promote cognitive deficits in the elderly. Here, we resolve age-dependent modulation of CSF dynamics and choroid plexus function by complementary in vivo determinations of intracranial pressure (ICP) and CSF secretion/absorption rates, combined with transcriptomic, morphological, and metabolic analysis of choroid plexus in aging male rats. ICP and CSF secretion rate and absorption capacity remain stable with age, and the choroid plexus retains its morphology, structural integrity, gene expression, and high metabolic rate across the tested ages. This work supports the significance of choroid plexus function for brain aging and promotes this tissue as a future target for neurodegenerative diseases associated with impaired waste clearance and cognitive decline.